115-3x+5x=11

Simple and best practice solution for 115-3x+5x=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 115-3x+5x=11 equation:


Simplifying
115 + -3x + 5x = 11

Combine like terms: -3x + 5x = 2x
115 + 2x = 11

Solving
115 + 2x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-115' to each side of the equation.
115 + -115 + 2x = 11 + -115

Combine like terms: 115 + -115 = 0
0 + 2x = 11 + -115
2x = 11 + -115

Combine like terms: 11 + -115 = -104
2x = -104

Divide each side by '2'.
x = -52

Simplifying
x = -52

See similar equations:

| 2[a+7]-7=9 | | 1+4x=-x-5 | | 2x+20=12x-60 | | 6x+62=10+14 | | 2t^3-9t^2-27=0 | | x^2+3x=117 | | 171-6x=30x+15 | | 34y+5=345 | | (8*20)2+(8*13)2-(5*3)3-(7*2)=x | | N*3=38 | | 101-6x=21x+23 | | 0=0.02d^2-2.6d+66.5 | | 4x^2-6x-12=0 | | -5+x+3=7 | | 10-2x-6=-x+5 | | (8*20)2+(8*13)2-(5*3)3-(7*2)= | | 50-2x=16x+16 | | 6x+6=106-10x | | 12x^2+19x=-5 | | (8*20)2+(8*13)2=X | | -7-9w=-7w-10 | | -5-6=-4x-(x+6) | | 9-x-2x=0 | | -5-6=-4-(x+6) | | (8*20)2=x | | N-15=22 | | x+3=40 | | 952=12d+28 | | 7x-4-3x=4x+8 | | -(7x-2)+5=3 | | 38-18=4(x-6) | | x-84=-0.5 |

Equations solver categories